Factors influencing the mandatory adoption of RFID: An empirical investigation from Australian livestock industry - Hossain, M.; Quaddus, Mohammed (ANZAM, 2011)
The purpose of this study is to examine the factors of RFID adoption in a mandatory environment.This paper presents the result of an empirical study that investigates the adoption behaviour of livestock farms in relation to Radio Frequency Identification (RFID) technology in the context ofAustralia. A mixed method consisting qualitative and quantitative research approach has been taken for this study. The finding of this study confirmed that external environment, technological characteristics, and organizational factors are significant for RFID adoption. Alternatively, expectations from RFID-adoption do not have an influence on RFID adoption when the adoption is mandatory.